Clinical Nursing Interventions and Their Contribution to Stability in Hemodialysis Patients with Chronic Kidney Disease - Erwinsyah; Inaya Nur Aini (Journal of Public Health Indonesian, 2026)
Chronic kidney disease is a progressive condition requiring long-term hemodialysis and is associated with a high risk of physiological instability. Clinical nursing interventions play a strategic role in maintaining patient stability during hemodialysis procedures. This study aimed to analyze the relationship and contribution of clinical nursing interventions to the stability of patients with chronic kidney disease undergoing hemodialysis. A quantitative approach with a cross-sectional observational analytic design was employed. The study sample consisted of patients receiving routine hemodialysis who met the inclusion criteria. Data were collected using structured observation sheets of nursing interventions and measurements of patient stability indicators, and analyzed using correlation and linear regression tests. The results demonstrated a positive and statistically significant relationship between clinical nursing interventions and patient stability. Regression analysis indicated that nursing interventions contributed significantly to patient stability after controlling for clinical factors. These findings confirm that clinical nursing interventions are a critical determinant of patient stability and safety in hemodialysis care. Strengthening evidence-based nursing practices is therefore recommended to improve the quality of hemodialysis services and clinical outcomes.